Analisis PVS Cloud pada Database Server - Aprianti Putri Sujana (Komputika : Jurnal Sistem Komputer, 2017)
Cloud Computing is an information technology service that can be used or accessed by customers through the Internet network. Cloud Computing is a computing / computing model, where resources such as processors / computing power, storage, networks, and software become abstract and are given as services on the network / internet using remote access patterns [5]. To find out how effective cloud computing is, analysis is carried out on the network. That is the VPS cloud network which is analyzed using QoS (Quality of Service). QoS is defined as a mechanism or way that allows services to operate according to their respective characteristics in IP (Internet Protocol) networks [2]. The QoS (Quality of Service) test results obtained according to TIPHON standards fall into the very good category.